The fundamental rules of risk management - Lewis, Nigel Da Costa (Chapman & Hall/CRC finance series, 2013)
"Taking on risk is like building a bomb: when you ignore the fundamental rules, you bury it alive. It will explode.Maybe not today or tomorrow, but one day it will explode. As you read through The Fundamental Rules of Risk Management, you will discover that the consequences to personal finances, professional careers, corporate survivability, and even nation states can be ruinous. In this thought-provoking text, Dr. Lewis provides examples and case studies to demonstrate how the rules of risk can work to protect and enhance investor value" -- Provided by publisher